Association of hematological coefficients with markers of inflammation and oxidative stress in schizophrenia: results of a pilot analysis - Zhakhongir A.u. Abdumannonov; Ilya S. Blokhin; Alexandra Yu. Kargina; Alexandra A. Demidova; Olga V. Kostina; Tatiana V. Zhilyaeva; Galina E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Relevance. To date, there is convincing evidence in favour of the immuno-inflammatory hypothesis of the etiopathogenesis of schizophrenia. As markers of immuno-inflammatory disorders in schizophrenia, a small number of studies have examined haematological indices (HI) and systemic inflammation coefficients (SIC): neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR) and platelet-lymphocyte ratio (PLR). Considering that HI may hypothetically reflect immuno-inflammatory processes in schizophrenia, it is relevant to assess their relationship with other known biochemical markers of inflammation and oxidative stress in this disease. The aim of this study was to evaluate the association of HI with biochemical markers of inflammation and oxidative stress in schizophrenia, as well as with the severity of clinical symptoms. Materials and methods: 50 patients with schizophrenia were examined: 42 women, 8 men, age 36 [7] years (median and interquartile range, hereafter Me [Q1; Q3]). Clinical assessment was performed using the Schizophrenia Positive and Negative Syndrome Scale and the Calgary Depression Scale for Schizophrenia. HI, homocysteine (Hc), tetrahydrobioterine (BH4), reduced glutathione (GSH), interleukin-6 (IL-6), C-reactive protein (CRP) and tumour necrosis factor-alpha (TNF-a) were studied. Results: Serum CRP levels were significantly correlated with leukocyte count, total monocyte, basophil and eosinophil counts, and granulocyte counts, but not with SIC (NLP, MLR and PLR). TNF-a has stronger direct correlations with a number of HI (granulocyte and erythrocyte counts, leukocyte counts at the level of trend towards significance) and coefficients (NLP, MLR at the level of trend). Conclusions: HI in the studied sample of patients with schizophrenia correlate with the data obtained by foreign authors, which indicates the prospect of studying this topic in the Russian population. Further evaluation of the relationship between HI (SIC) and serum TNF-a seems relevant. The study of associations of biochemical immuno-inflammatory markers with SIC further requires a thorough assessment of the stage of disease development, duration of its course, peculiarities of response to therapy.